Peran Kode Etik Kepolisian dalam Mencegah Penyalahgunaan Wewenang - Fadhil Citra Darmakusuma; Muhammad Afrizal Habibie; Nauval Athalah Ramadani; Raja Huwaidi Kamil; Baidhowi Baidhowi (Jurnal Kajian Hukum Dan Kebijakan Publik | E-ISSN : 3031-8882, 2026)
The Police Code of Ethics serves as a moral and professional guideline that must be upheld by every police officer in carrying out their duties and authority. This article aims to analyze the role of the Police Code of Ethics in preventing the abuse of authority by law enforcement officers. The research method used is a normative juridical approach by examining laws and regulations, legal doctrines, and relevant literature. The study finds that the Police Code of Ethics functions as an effective internal control instrument in fostering integrity, accountability, and professionalism among police officers. Furthermore, the strict enforcement of ethical sanctions against violations plays an important role in creating a deterrent effect and maintaining public trust. However, there are still challenges in its implementation, such as weak supervision and organizational culture that does not fully support ethical enforcement. Therefore, it is necessary to strengthen the supervisory system, improve the quality of human resources, and enhance institutional commitment to ensure that the Police Code of Ethics functions optimally in preventing the abuse of authority.